A study of the bone marrow derived mesenchymal stromal cells in rats – proliferation and immunophynotypic markers - Mauida, F. Hasoon (2020)
Mesenchymal stem cells derived from bone marrow (BM-MSCs) have the ability to differentiate into multiple cell lineages. Although the cultivation of these cells has led to a number of characterisation studies, some significant morphological and immunohistochemical properties are still lacking. In this study, isolation of BM-MSCs, morphological features, cell viability, immunophenotypic properties and cryopreservation of BM-MSCs were examined in detail. The results demonstrate that the cells isolated from BM-MSCs were plastic adherent and had fibroblastic spindle shape after three passages and get confluent monolayer cells 70-80% after 4-7 days post-subculture. Based on the cell viability analysis, the BM-MSCs showed an increase in cell viability starting from passage 1 until passage 10. Immunophenotypic analysis demonstrated that BM-MSCs were positive for CD44 and CD105 and negative for CD34. Functional analysis of cryopreservation of BM-MSCs from P6 after 6 months expressed good proliferation rate and cell viability.